Smad7 Inhibits Transforming Growth Factor-β Family Type I Receptors through Two Distinct Modes of Interaction - Kamiya, Yuto (American Society for Biochemistry and Molecular Biology, 2010)
The inhibitory Smads (I-Smads), i.e. Smad6 and Smad7, are negative regulators of transforming growth factor-β (TGF-β) family signaling. I-Smads inhibit TGF-β family signaling principally through physical interaction with type I receptors (activin receptor-like kinases), so as to compete with receptor-regulated Smads (R-Smads) for activation. However, how I-Smads interact with type I receptors is not well understood. In the present study, we found that Smad7 has two modes of interaction with type I receptors. One is through a three-finger-like structure in the MH2 domain, consisting of residues 331–361, 379–387, and the L3 loop. The other is through a basic groove in the MH2 domain (Mochizuki, T., Miyazaki, H., Hara, T., Furuya, T., Imamura, T., Watabe, T., and Miyazono, K. (2004) J. Biol. Chem. 279, 31568–31574). We also found that Smad6 principally utilizes a basic groove in the MH2 domain for interaction with type I receptors. Smad7 thus has an additional mode of interaction with TGF-β family type I receptors not possessed by Smad6, which may play roles in mediating the inhibitory effects unique to Smad7.